Interactions between Stimulus-Specific Adaptation and Visual Auditory Integration in the Forebrain of the Barn Owl - Reches, Amit (J Neurosci, 2010)
Neural adaptation and visual auditory integration are two well studied and common phenomena in the brain, yet little is known about the interaction between them. In the present study, we investigated a visual forebrain area in barn owls, the entopallium (E), which has been shown recently to encompass auditory responses as well. Responses of neurons to sequences of visual, auditory, and bimodal (visual and auditory together) events were analyzed. Sequences comprised two stimuli, one with a low probability of occurrence and the other with a high probability. Neurons in the E tended to respond more strongly to low probability visual stimuli than to high probability stimuli. Such a phenomenon is known as stimulus-specific adaptation (SSA) and is considered to be a neural correlate of change detection. Responses to the corresponding auditory sequences did not reveal an equivalent tendency. Interestingly, however, SSA to bimodal events was stronger than to visual events alone. This enhancement was apparent when the visual and auditory stimuli were presented from matching locations in space (congruent) but not when the bimodal stimuli were spatially incongruent. These findings suggest that the ongoing task of detecting unexpected events can benefit from the integration of visual and auditory information.